2006
DOI: 10.1007/s11293-006-6130-x
|View full text |Cite
|
Sign up to set email alerts
|

Dueling Jackpots: Are Competing Lotto Games Complements or Substitutes?

Abstract: This paper considers the relationship that exists between two lottery products offered simultaneously in the same state, a smaller lottery game run by the individual state and a larger multi-state game run in coordination with other states. The primary issue is whether the two different products should be considered substitutes or complements for one another. The question is considered from two different perspectives that lead to a conclusion that while the two products do tend to be complements to one another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 10 publications
0
39
1
Order By: Relevance
“…Of the 19 study observations analysed, 13 indicated substitution (Brown & Rork, 2005;Farrell & Forrest, 2008;Fink & Rork, 2003;Forrest, Gulley, & Simmons, 2004;Garrett & Marsh, 2002;Grote & Matheson, 2006;Mikesell & Zorn, 1987;Roger & Chabi, 2009;Stover, 1990;Tosun & Skidmore, 2004;Walker & Jackson, 2008), two found a complementary relationship (Forrest & McHale, 2007;Purfield & Waldron, 1999), and four found no impact (Farrell & Forrest, 2008;Forrest et al, 2004;Gulley & Scott, 1993;Lin & Lai, 2006). This result indicates that intra-product cannibalization (Srinivasan et al, 2005) is common in the lottery markets.…”
Section: Lotteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 study observations analysed, 13 indicated substitution (Brown & Rork, 2005;Farrell & Forrest, 2008;Fink & Rork, 2003;Forrest, Gulley, & Simmons, 2004;Garrett & Marsh, 2002;Grote & Matheson, 2006;Mikesell & Zorn, 1987;Roger & Chabi, 2009;Stover, 1990;Tosun & Skidmore, 2004;Walker & Jackson, 2008), two found a complementary relationship (Forrest & McHale, 2007;Purfield & Waldron, 1999), and four found no impact (Farrell & Forrest, 2008;Forrest et al, 2004;Gulley & Scott, 1993;Lin & Lai, 2006). This result indicates that intra-product cannibalization (Srinivasan et al, 2005) is common in the lottery markets.…”
Section: Lotteriesmentioning
confidence: 99%
“…Grote and Matheson (2006) suggested that multistate lotteries cannibalize some of the sales from state lotteries, but that the overall benefit for lottery companies is positive.…”
Section: Lotteriesmentioning
confidence: 99%
“…An early example of substitution-cross price effects-between different gambling activities is Forrest et al (2005) in the case of betting and lotto. Grote and Matheson (2006) found evidence of both complementarities and substitution between a single state lotto and a larger jackpot (highest payoff) multi-state lotto. This article can be thought of as an investigation of the micro-foundations of the results in Grote and Matheson (2006).…”
mentioning
confidence: 94%
“…Grote and Matheson (2006) found evidence of both complementarities and substitution between a single state lotto and a larger jackpot (highest payoff) multi-state lotto. This article can be thought of as an investigation of the micro-foundations of the results in Grote and Matheson (2006). Their discussion of the issue of substitutes versus complements in lottery games, based on their examination of the relationship between a multi-state and a single state lottery game, informs our analysis.…”
mentioning
confidence: 94%
See 1 more Smart Citation